Pengaruh Profitabilitas, Likuiditas, Earning Per Share (EPS) dan Covid-19 (Sebagai Variabel Dummy) terhadap Harga Saham Perusahaan Perbankan yang Terdaftar di BEI Tahun 2016-2022 - Nanda Aisyah Rissema; Gregorius N.Masdjojo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The COVID-19 pandemic hit Indonesia in 2020, the world Composite Stock Price Index (IHSG) decreased drastically in 2020. Indonesia's IHSG fell significantly in March, after information about Covid-19 entered Indonesia. Shares are the highest risk and riskiest among investment instruments. Share prices are formed based on an agreement between demand and supply for traded shares. The share price shows the issuer's performance, share price movements are in line with the issuer's performance, and the issuer's share price tends to rise by investors. Based on the results of the research and discussion, it was concluded that ROA, EPS and COVID-19 had no effect on the share prices of banking companies listed on the IDX Indonesia Stock Exchange. The Current Ratio has an influence on the share prices of banking companies listed on the IDX. The influence of the Current Ratio shows that the company is able to manage current debt with the current assets it owns even though Covid-19 is currently hitting Indonesia.